SENGKETA AKIBAT PEMUTUSAN KERJA SAMA ANTARA PT. SARANA INVESTAMA MANGGABAR DENGAN PROVINSI NUSA TENGGARA TIMUR - Angelina Bernadina Linojawa Keban (Gapenas Publisher, 2022)
Basically, humans are social creatures (zoon politicon) who interact with each other. The increasingly rapid interaction of the community often leads people to bind themselves with other communities, resulting in making an agreement. Agreement is one of the legal studies that is always evolving, along with the development of society. Onong Uchana Effendy in his book Communication Science Theory and Practice reveals that